2017
DOI: 10.1021/acsphotonics.7b01026
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Modulated Raman Spectroscopy

Abstract: The coupling of plasmonic and mechanical properties at the nanoscale is of great potential for the development of next generation devices capable to detect weak forces, mass changes, minute displacements and temperatureinduced effects. Both the transduction of mechanical motion to the scattered light fields in term of polarization or intensity modulation and plasmon-driven mechanical oscillations have already been demonstrated. Quasi static tunable hot spots have recently been designed and applied to surface-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The glancing angle at which the deposited material encounters the surface produces an array of posts all oriented toward the evaporation source. These nanoposts were demonstrated to be efficient SERS substrates for analytical applications, showing an EF of 10 8 . , In addition, to generate a large SERS enhancement, the anisotropic and ordered nature of the nanorod structures make them sensitive to the polarization of the incident light. , Other reports have demonstrated the polarization response of SERS signals in various structures, such as nanogaps (e.g., nanoparticles dimers) and anisotropic nanoparticles. Previous work by Brolo’s group has used the SERS polarization response of plasmonic microarrays to subtract unwanted background from Raman spectra. …”
mentioning
confidence: 99%
“…The glancing angle at which the deposited material encounters the surface produces an array of posts all oriented toward the evaporation source. These nanoposts were demonstrated to be efficient SERS substrates for analytical applications, showing an EF of 10 8 . , In addition, to generate a large SERS enhancement, the anisotropic and ordered nature of the nanorod structures make them sensitive to the polarization of the incident light. , Other reports have demonstrated the polarization response of SERS signals in various structures, such as nanogaps (e.g., nanoparticles dimers) and anisotropic nanoparticles. Previous work by Brolo’s group has used the SERS polarization response of plasmonic microarrays to subtract unwanted background from Raman spectra. …”
mentioning
confidence: 99%
“…A similar approach was recently used. Greco et al reported on the exploitation of mechanical resonances in a cantilever to study the plasmonic amplification of a single hotspot with modulated Raman spectroscopy …”
Section: Resultsmentioning
confidence: 99%
“…Greco et al reported on the exploitation of mechanical resonances in a cantilever to study the plasmonic amplification of a single hotspot with modulated Raman spectroscopy. 27 Spatial Resolution below 10 nm. The spatial resolution of this system is obtained from the cross-sectional analysis in Figure 2.…”
Section: Acs Photonicsmentioning
confidence: 99%
“…As a widely used and powerful characterization method, Raman spectroscopy can preliminarily understand the phono information of synthetic crystals [21] . We characterized the NbAs crystals by Raman spectroscopy, shown in Figure 2(b) of bulk NbAs crystals, which mainly displayed three prominent Raman peaks in the range of 180-330 cm -1 .…”
Section: Materials Characterizationmentioning
confidence: 99%